Determination of Chlorpromazine Using Molecular Imprinting Polymers in Different Sample Matrices - Ammen, Eman Wajeh; Al-Bayati, Yehya Kamal (Universitas Gadjah Mada, 2024)
Antipsychotic drugs, including chlorpromazine, are frequently used to treat mental illnesses. However, prolonged exposure to even small amounts of the substance can accumulate and cause a potential human health risk. Thus, the selective and sensitive detection of these drugs is crucial. Molecularly imprinted polymers (MIPs) are receptors that are designed to have a highly specific molecular recognition ability, which is the primary and crucial function of receptors. The synthesis of chlorpromazine-imprinted polymers involves the polymerization of functional monomers and cross-linkers in the presence of chlorpromazine as a template, followed by the removal of the template to create cavities with complementary binding sites. Various strategies, including bulk polymerization, free radical polymerization surface imprinting, and nanoimprinting, have been employed to fabricate chlorpromazine-molecular imprinted polymers with high affinity and selectivity. Characterization techniques such as UV-vis spectroscopy, Fourier-transform infrared spectroscopy, and scanning electron microscopy are commonly employed to confirm the successful imprinting of chlorpromazine. The high selectivity of MIP toward templates enables them to be used in various applications like solid-phase extraction and chemical sensors, among others. The aim of this review is to present and highlight the various methods used to determine chlorpromazine based on molecular imprinting polymers in different samples.